Fenomena Perilaku Body Shaming di Kalangan Perempuan pada Mahasiswi Fakultas Ushuluddin dan Filafat UIN Alauddin Makassar - Zakiyah Muallifah; Wahyuni Wahyuni; Dewi Anggariani (SOSIORELIGIUS, 2020)
The results showed that, the forms of body shaming experienced are face shaming, fat shaming and skinny shaming. The impacts of body shaming behavior include negative impacts, namely going on a strict diet, causing discomfort in the victim, avoiding the social environment and affecting social relationships, and lowering confidence.  The positive impact of body shaming is to be a motivation to the victim as well as to take better care of the body. Sorority's view of body shaming behavior, as a Muslim should avoid reproach because denouncing acts are prohibited in religion and can cause adverse effects especially to victims and divisions among others in addition to denouncing each other just as we denounce the creation of Allah swt.